Follicular Wave Synchronization Using GnRH Agonist in Jersey Crossbred Cows - SATHESH KUMAR, S; PALANISAMY, A; RAMADAS, P; SUBRAMANIAN, A; KATHIRESAN, D (The Indian Journal of Animal Reproduction, 2023)
The study was aimed at recording the synchronization of follicular wave emergence in Jerseycrossbred cows when administered with GnRH on Day 5 of the cycle. initially, as a control study, thenormal follicular wave pattern were studied in Jersey crossbred cows (n=6) using ultrasound scanner.During the subsequent cycle, all the animals were injected with GnRH agonist - Buserelin acetate (Inj.Receptal; 10 μg i.m.) on Day 5 of the cycle and follicular wave pattern was studied: Monitoring thenormal follicular wa've pattern revealed that, out of six cows, three cows (50%) exhibited two waves andthree (50%) exhibited three waves per cycle with the mean days of emergence on 1.33 ± 0.90 and I 0.0 ±0.34 and 1.67 ± 0.34, 9.67 ± 0.67 and 15.33 ± 0.88 respectively. Administration ofGnRH on day 5 ofthe cycle caused ovulation of dominant follicle (8.92 ± 0.60 mm) a new follicular wave emerged by twodays of GnRH administration (Day7) in all the animals. In response to the GnRH administration normaltwo wave cycles were altered to three wave cycles with the third wave emerging on the mean day of14.6± 1.20 and there was no significant change among the three wave cycles. There was no significantdifference in the cycle length among the normal and GnRH treated cows (22.50 ± 0.83 vs 21.33 ± 1.49days).
Keywords: Follicular wave synchronization - GnRH - Jersey crossbred cows